Film as a mass communication media: Analysis of moral messages through Omar Hana's film - M. Ali Sibram Malisi; Surawan Surawan; Sayyidatul Hasanah; Siti Zaida Hanum (Universitas Negeri Yogyakarta, 2023)
Morals are a very important element in a person's life because someone who has character means having a benchmark for the quality of his personality. Moral education can be instilled in various ways, one of which is through technological sophistication. Technology that can be said to be not new and growing rapidly is film. One of the films that entertain and educate today is the animated film, Omar and Hana. The purpose of this research is to analyze what are the values of moral education in the animated film Omar and Hana. This study uses a qualitative research approach with library research methods. The data sources used are primary data sources and secondary data sources. Data collection techniques used are observation and documentary techniques. The data analysis technique used the semiotic analysis of the Roland Barthes model. The results of this study indicate that the values of moral education contained in the animated films of Omar and Hana episodes